The Role of Codon Usage, tRNA Availability, and Cell Proliferation in EBV Latency and (Re)Activation - Kanduc, Darja (Global Medical Genetics, 2022)
Epstein–Barr nuclear antigen 1 (EBNA1) protein synthesis is inhibited during Epstein–Barr virus (EBV) latency and is resumed in EBV (re)activation. In analyzing the molecular mechanisms underpinning the translation of EBNA1 in the human host, this article deals with two orders of data. First, it shows that the heavily biased codon usage of the EBNA1 open reading frame cannot be translated due to its noncompliance with the human codon usage pattern and the corresponding tRNA pool. The EBNA1 codon bias resides in the sequence composed exclusively of glycine and alanine, i.e., the Gly-Ala repeat (GAR). Removal of the nucleotide sequence coding for GAR results in an EBNA1 codon usage pattern with a lower codon bias, thus conferring translatability to EBNA1. Second, the data bring cell proliferation to the fore as a conditio sine qua non for qualitatively and quantitatively modifying the host's tRNA pool as required by the translational needs of EBNA1, thus enabling viral reactivation. Taken together, the present work provides a biochemical mechanism for the pathogen's shift from latency to (re)activation and confirms the role of human codon usage as a first-line tool of innate immunity in inhibiting pathogens' expression. Immunologically, this study cautions against using codon optimization and proliferation-inducing substances such as glucocorticoids and adjuvants, which can (re)activate the otherwise quiescent, asymptomatic, and innocuous EBV infection. Lastly, the data pose the question whether the causal pathogenic role attributed to EBV should instead be ascribed to the carcinogenesis-associated cellular proliferation.
Keywords: EBNA1 translation; GAR; codon usage; tRNA availability; cell proliferation; adjuvants